2008
DOI: 10.1103/physreva.77.045402
|View full text |Cite
|
Sign up to set email alerts
|

Zitterbewegungby quantum field-theory considerations

Abstract: The validity of the work by Lamata et al. ͓Phys. Rev. Lett. 98, 253005 ͑2007͔͒ can be further shown by quantum field-theory considerations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 10 publications
0
22
0
Order By: Relevance
“…In quantum field theory, a superposition of positiveand negative-energy wave functions is deemed physically impossible. However, a hole theory [6,37] describes that a hole can be seen as a positron, and Wang and Xiong [11] argued that therefore quantum field theory may still allow the existence of Zitterbewegung.…”
Section: Dirac Equation Vs Dirac-like Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…In quantum field theory, a superposition of positiveand negative-energy wave functions is deemed physically impossible. However, a hole theory [6,37] describes that a hole can be seen as a positron, and Wang and Xiong [11] argued that therefore quantum field theory may still allow the existence of Zitterbewegung.…”
Section: Dirac Equation Vs Dirac-like Systemmentioning
confidence: 99%
“…However, this concept is controversial and was challenged by Krekora et al [10]. The existence of Zitterbewegung, in relativistic quantum mechanics and in quantum field theory, has been a recurrent subject of discussion over the past years [10][11][12]. The interest in Zitterbewegung was recently rekindled due to its analog in Dirac-like systems [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…[33] using a different approach. For many systems [5,[7][8][9][10][11][12][13][14][15][16][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] the Hamiltonian can be written in a quite general form:…”
Section: Spin In An Effective Magnetic Fieldmentioning
confidence: 99%
“…It arises as an interference effect between the positive and negative energy parts of the spinor and does not appear for spinors that consist entirely of positive (or negative) energy. The real existence of Zitterbewegung, in relativistic quantum mechanics and in quantum field theory, has been a recurrent subject of discussion in the last years [24,25]. Lamata et al suggested [18] that the physics of a free Dirac particle could be simulated using an ion with four internal states and a set of laser beams coupling these states to the three harmonic oscillators describing the ion motion in the trapping potential.…”
Section: Introductionmentioning
confidence: 99%